Body composition and bone mineral density of Division 1 collegiate track and field athletes, a Consortium of College Athlete Research (C-CAR) study - Dengel, D. R.; Keller, K. A.; Stanforth, P. R.; Oliver, J. M.; Bosch, T. A. (Journal of Clinical Densitometry, 2020)
The purpose of the present study was to generate normative values for total and regional body composition in male and female Division 1 collegiate track and field athletes using dual X-ray absorptiometry. We also sought to examine body composition by event and sex. Data were used from the Consortium of College Athlete Research group. A total of 590 (male [M]/female [F]=274/316) athletes had their height, weight, total and regional fat mass (FM), lean mass, and bone mineral density (BMD) measured. Athletes were classified into 1 of 7 categories: Jumps (M/F=28/30); Long Distance (M/F=104/110), Middle Distance (M/F=27/24), Multievent (M/F=11/9), Pole Vault (M/F=21/27), Sprints (M/F=54/96), and Throws (M/F=29/20). Total and regional differences between events and sex were assessed by analysis of variance. Except for male and female throwers, all other track and field athletes` mean percent body fat (M: 10.3%-12.6%, F: 17.5%-21.6%) and visceral FM (<500 g) was low, but in a healthy range. As expected, throwers had significantly (p < 0.05) higher total and regional FM and lean mass than other events. In addition, male (1.55 ± 0.11 g/cm2) and female (1.40 ± 0.12 g/cm2) throwers had significantly greater BMD than all other events while male (1.25 ± 0.10 g/cm2) and female (1.16 ± 0.09 g/cm2) distance runners had significantly lower BMD than all other events. In conclusion, track athletes` body composition differed across events for both males and females. These measurements provide normative data on NCAA Division 1 male and female track and field athletes.